A Literature Review on the Correlation Between Shear Bond Strength and the Degree of Conversion of Orthodontic Adhesive Systems - Ziad S. Abdul Majid; Azza El Badry (European Scientific Journal, ESJ, 2016)
Objectives: The purpose of this study is to provide a comprehensive literature review on the correlation between shear bond strength and the degree of conversion of the orthodontic adhesive systems. Thus, this is considered as a major issue for the success of the orthodontic bonding techniques. Material and Methods: Electronic searches were performed in Pubmed and Scopus databases using relevant keywords. Textbook searching was also applied. Following the selection, full-text English language papers were fully reviewed to ensure that they met both the inclusion and the exclusion criteria. Results: Recent studies suggest that when increasing the DC, the SBS will increase. Thus, this results to a stiffer and a more durable resin. Conclusions: There is a wide range of factors affecting the SBS, DC, and their correlation. Some of them are related to the tooth etching techniques, adhesive related factors, curing units, and bracket materials. More research is required to develop more understanding of the role of these factors in determining the bonding success. This is because there are no specific published papers which were directly linked to the correlation between the SBS and the DC of orthodontic adhesives.